1997
DOI: 10.1590/s0103-50531997000500010
|View full text |Cite
|
Sign up to set email alerts
|

A HF/CI-SD study of the low-lying states of nitroprusside ion

Abstract: Desde a descoberta de dois estado meta-estáveis gerados por excitação ótica do nitroprussiato de sódio cristalino, Na2[Fe(CN)5NO].2H2O (SNP), exibindo longa meia-vida a temperaturas abaixo de 160 K, grande esforço vem sendo realizado no sentido de entender a estrutura eletrônica de sistemas correlatos. Apesar deste esforço, a natureza dos orbitais de fronteira e dos processos de excitação eletrônica de baixa energia são, ainda hoje, controversos. Cálculos iniciais EHT mostram que o HOMO possuia caráter do orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Fenske-Hall-type calculations 27 of SNP and other first-row transition-metal nitrosylpentacyanides similarly indicated the HOMO to be a b 2 orbital of mostly metal d xy character with some π(CN cis ) contribution. The assignment was compatible with the interpretation of a variety of experimental results obtained with the ESR, 28 XPS, 26 XANES, 18 polarized absorption, 9,26 and Mo ¨ssbauer 28 techniques.…”
Section: Orbital Ordering Of the Snp Ground-state Speciessupporting
confidence: 85%
See 1 more Smart Citation
“…Fenske-Hall-type calculations 27 of SNP and other first-row transition-metal nitrosylpentacyanides similarly indicated the HOMO to be a b 2 orbital of mostly metal d xy character with some π(CN cis ) contribution. The assignment was compatible with the interpretation of a variety of experimental results obtained with the ESR, 28 XPS, 26 XANES, 18 polarized absorption, 9,26 and Mo ¨ssbauer 28 techniques.…”
Section: Orbital Ordering Of the Snp Ground-state Speciessupporting
confidence: 85%
“…They were set aside by the authors because of the disagreement with the experimental results listed above, though they are supported by subsequent HF results. The HF/CI-SD calculations 28 of Hollauer and Olabe assign the first electronic transition to ligand-to-ligand charge transfer from axial-cyano to the nitrosyl ligand, the e-type HOMO being composed of CN orbitals with about 70% axial-CN character. The excitation energy of d xz,yz f π*-(NO) and d xy f π*(NO) transitions were calculated with the ∆SCF method (including CI) as 4.52 and 5.04 eV, which is in good agreement with the spectroscopic observations.…”
Section: Orbital Ordering Of the Snp Ground-state Speciesmentioning
confidence: 99%
“…NO orbitals also mix with those of Fe to define the LUMOs. This description resembles several ones previously given, which have been obtained by means of different methodologies with no consideration of the solvent and also with the DFT calculations performed in this work for isolated [Fe(CN) 5 NO] 2- . In this way, lack of modeling the solvent seems to be the origin of the controversy among the related data.…”
Section: Resultssupporting
confidence: 68%
“…This alteration reflects the loss of electron density of the CNgroup and accumulation of electron density of the NO + upon complex formation. 29 Appropriate calculations, which make use of a Mulliken population analysis, 30 found that for both the cyanide and the nitrosyl ligands the electronic structures of the 3σ, 4σ, and 1π orbitals were unchanged as compared with those of the free ions. Only the 5σ and 2π orbital occupancies appear to be affected by complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…However, It is well known that there are intramolecular environmental effects, caused by the central atom, in the energy levels and electronic distributions, as illustrated by the fact that the magnitudes of the separations are not nearly as large as those in the isolated ligands (CN − and NO + ). This alteration reflects the loss of electron density of the CN − group and accumulation of electron density of the NO + upon complex formation . Appropriate calculations, which make use of a Mulliken population analysis, found that for both the cyanide and the nitrosyl ligands the electronic structures of the 3σ, 4σ, and 1π orbitals were unchanged as compared with those of the free ions.…”
Section: Resultsmentioning
confidence: 99%